Evaluation of Therapeutic Potential of Chenopodium Album L. Extract Against Cyclophosphamide Induced Reproductive Damages in Male Rats - Kumar Verma, Manish; Hasan Ahmad, Abul; Prasad, Niharika (The Indian Journal of Animal Reproduction, 2025)
Chenopodium album, a leafy plant belonging to the family Amaranthaceae, is highly nutritious and holds significant medicinal value. Traditionally, it is recognized for its antioxidant, anti-parasitic, immunostimulant, antimicrobial, and anti-inflammatory properties. This study investigates the therapeutic potential of hydroethanolic extract of C. album (CAHE) against cyclophosphamide (CYP)-induced reproductive toxicity in male albino rats. CYP, a cytotoxic chemo therapeutic agent, is known to induce oxidative stress, impair sperm quality, and disrupt hormonal balance. The study employed various reproductive and oxidative stress parameters to assess the protective effects of CAHE. Results revealed that CAHE significantly (p<0.05) attenuated CYP-induced oxidative stress, as indicated by reduced lipid peroxidation (LPO) and restoration of antioxidant markers such as glutathione (GSH) and catalase. CAHE also markedly improved sperm motility, viability, density, and morphology in CYP-treated rats, demonstrating its potential as a natural therapeu tic agent for mitigating chemotherapy-associated reproductive toxicity.